South African unemployment: the case of the geoscience graduates - Mkhize, Nomvelo Pumla (University of the Witwatersrand, Johannesburg, 2023)
Unemployment presents a substantial global challenge, and South Africa is no exception, consistently reporting one of the highest unemployment rates, particularly among its youth population. The recent pandemic has further worsened this situation, notably reflected in the growing difficulties geoscience graduates encounter in finding employment upon graduation. This study aimed to assess the factors contributing to the growing number of geoscience graduates struggling to secure employment from the human resources (HR) perspective. The study assesses the mismatch between the skills required by the job market versus the skills produced by the universities. A need for partnerships and collaborations between industry and universities to improve the skills and employability of graduates is identified. The study delineates the roles and responsibilities of key stakeholders to remedy the geoscience graduate unemployment problem and proposes strategies for augmenting graduates' expertise, employability, and skill sets. The study utilised a qualitative design incorporating semi-structured, semi-structured open-ended interviews with the human resources officer (s). Thematic analysis was conducted on the data to understand the perceptions and perspectives of the HR officers. This study reveals that there are several factors perceived to be attributed to the rising geoscience graduate unemployment, and these include, inter alia, a considerable misalignment regarding the skills the universities are producing versus the skills required by the job market, the lack of collaboration and partnership between the key stakeholders (i.e. universities, industry, and government) and the misalignment between the available job opportunities and the available graduates. Therefore, this calls for more collaborations and partnerships to solve the problem of geoscience graduate unemployment. This research study is, thus, intended to provide a fresh perspective for policymakers, the geoscience industry and higher education institutional leaders
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Geoscience; geoscientists; unemployment; geoscience graduates’ unemployment; mining industry; and graduate; SDG-8: Decent work and economic growth